The effect of award on CSR disclosures in annual reports of Malaysian PLCs - Anas, Abdirahman; Abdul Rashid, Hafiz Majdi; Annuar, Hairul Azlan (Emerald Group Publishing Limited, 2015)
Purpose – The paper aims to examine the determinants of corporate social responsibility (CSR) disclosures in the annual reports of Malaysian public listed companies (PLCs). In 2006, Bursa Malaysia Berhad (BMB) launched its CSR Framework (effective in 2007) which is supposed to guide the Malaysian PLCs’ CSR disclosures. It is believed that this CSR framework may influence CSR disclosuresto be more systematic, yet there is no evidence whether this framework influences the extent and quality of CSR disclosures. Thus, this study examines this area of research. The study also tests the influence of award on CSR disclosures.